Theoretical and experimental study on conveying behavior of a twin-screw multiphase pump. (August 2016) - Hu, Bin; Cao, Feng; Yang, Xiaoqiang; Wang, Xiaolin; Xing, Ziwen
In this paper, the conveying behavior of a twin-screw multiphase pump is investigated when it pumps either pure water or gas–liquid mixtures with gas void fractions varying from 20% to 90%. A prototype of the twin-screw multiphase pump is developed and set up in a laboratory for this purpose. A theoretical model is established to evaluate backflow rates in the twin-screw pump clearances, total pump volume flow rates, and power consumptions at various pressure differences and gas void fractions. Results show that the predictions from the model agree well with experimental data. For pumping pure water, the power consumption increases by 45.3% when the pressure difference between inlet and outlet of the twin-screw multiphase pump increases from 0.6 to 1.0 MPa. However, the effect of the pressure difference on the total pump flow rate is negligible. For pumping air–water mixtures, the pressure difference has a significant effect on both power consumption and total volume flow rate of the multiphase pump. The pump power consumption increases by more than 40% when the pressure difference increases from 0.4 to 1.0 MPa. On the contrary, the pump volume flow rate decreases between 10% and 30% varying with the gas void fraction value. However, at the fixed pressure differences of 0.4 MPa and 1.0 MPa, the pump power consumption does not show much difference with the change of gas void fractions from 20% to 90% although the total pump volume flow rate reduces by 18.7% and 25.7%, respectively.